5(2x-6)-3=5(x-3)+2

Simple and best practice solution for 5(2x-6)-3=5(x-3)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-6)-3=5(x-3)+2 equation:


Simplifying
5(2x + -6) + -3 = 5(x + -3) + 2

Reorder the terms:
5(-6 + 2x) + -3 = 5(x + -3) + 2
(-6 * 5 + 2x * 5) + -3 = 5(x + -3) + 2
(-30 + 10x) + -3 = 5(x + -3) + 2

Reorder the terms:
-30 + -3 + 10x = 5(x + -3) + 2

Combine like terms: -30 + -3 = -33
-33 + 10x = 5(x + -3) + 2

Reorder the terms:
-33 + 10x = 5(-3 + x) + 2
-33 + 10x = (-3 * 5 + x * 5) + 2
-33 + 10x = (-15 + 5x) + 2

Reorder the terms:
-33 + 10x = -15 + 2 + 5x

Combine like terms: -15 + 2 = -13
-33 + 10x = -13 + 5x

Solving
-33 + 10x = -13 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-33 + 10x + -5x = -13 + 5x + -5x

Combine like terms: 10x + -5x = 5x
-33 + 5x = -13 + 5x + -5x

Combine like terms: 5x + -5x = 0
-33 + 5x = -13 + 0
-33 + 5x = -13

Add '33' to each side of the equation.
-33 + 33 + 5x = -13 + 33

Combine like terms: -33 + 33 = 0
0 + 5x = -13 + 33
5x = -13 + 33

Combine like terms: -13 + 33 = 20
5x = 20

Divide each side by '5'.
x = 4

Simplifying
x = 4

See similar equations:

| -9x^2+12-4=0 | | 10p-2(3p-6)=4(5p-6)-10 | | -96-8= | | b+0.08=-1 | | 11x=5x+66 | | 90/h=10 | | Y=4x+ax+6 | | n-55=23 | | 5x+y=168 | | 3x-x=-1 | | 7(6x+3)=21+5x | | 2h+5=9 | | x+78=149 | | z=9/4=2 | | 3x+22-z=162 | | 11*x+4x=5*x+70 | | X+20=16X-48 | | 19x-5=13x-17 | | 1-5/8x8 | | 7x-5+6x+8= | | X+20=2X-6 | | 9/9.1=n/14.8 | | V^2/25=12 | | 2x^2+50=10 | | 16x-12x-21=6x-2x-21 | | 2=6-2z | | b^3-b^2-56b=0 | | 36u=576 | | 4x-8/x-2 | | 2*(10+g)= | | 3x=5(25-7) | | 10x+15y=4290 |

Equations solver categories